Driving change through diversity and globalization : transformative leadership in the academy - Anderson, James A. (James Alan), 1948- (Sterling, Va. : Stylus Pub., 2008)
"This book argues that success in meeting challenges will be achieved to the degree that institutions embed the twin values of diversity and globalism at the heart of their activities. James Anderson demonstrates how focusing on these two values - that each institution needs to define collectively for itself to gain commitment and active engagement at every level - will drive the transformation essential to meeting tomorrow's demands." "By setting out the challenges and considerations that must be addressed by administrative leaders, by faculty, by trustees, and by others who shape the vision and direction of the institution, the author offers a framework to place the diversity discussion in a learning-centered context. While charging institutional leaders with the responsibility for organizational change, he stresses the critical role of chief academic officers and faculty in changing the teaching and learning paradigm, transforming the curriculum, and empowering the voices of diverse students. He calls for strategically linking diversity and globalism to teaching and learning outcomes." "This book significantly advances discussion of the mission of higher education in today's multicultural environment and global economy. It offers a strategic vision of success and practical ideas for creating transformative change, as well as a roadmap to implementing inclusive pedagogical practices and curricula."--BOOK JACKET.
Defining diversity in learning-centered contexts -- Shifting the organizational perspective on diversity : institutional and academic change -- Shaping the academic discussion about diversity -- Accounting for diversity within the teaching and learning paradigm -- Practical teaching strategies that engage student differences -- Balancing the traditional curriculum with inclusion and diversity -- Empowering the voice of diverse students in the college classroom -- Responsibility and accountability : a willingness to examine our promises and processes -- Appendix A. Summary of findings in relation to research questions -- Appendix B. Perceptions of academic leadership and competency and diversity outcomes -- Appendix C. Organizational assessment of diversity and leadership -- Appendix D. Student survey on classroom environment.
Includes bibliographical references and index.
Keywords: Multicultural education -- United States; Education, Higher -- Curricula -- United States; Education and globalization -- United States